2021
DOI: 10.1177/2150132721993651
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Social Determinants of Health Identified by Systematic Screening in a Medicaid Accountable Care Organization: A Qualitative Study

Abstract: Introduction/Objectives: Systematic screening for social determinants of health (SDOH), such as food and housing insecurity, is increasingly implemented in primary care, particularly in the context of Accountable Care Organizations (ACO). Despite the importance of developing effective systems for SDOH resource linkage, there is limited research examining these processes. The objective of the study was to explore facilitators and barriers to addressing SDOH identified by systematic screening in a healthcare sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…The remainder reported using observational study designs (eg, pre-post studies, feasibility studies, pilot studies). Fifty-eight studies were conducted with primary care patients, [29][30][31][72][73][74]76,[78][79][80][81][82][83][84][85][86][87][88][89] 4 took place in a specialty clinics, 32,71,75,77 1 took place in urgent care, 27 and 3 took place across multiple settings (eg, primary, specialty, and urgent care). 26,28,90 Majority of studies reported including academic sites (n = 40), 29,[34][35][36][37][38][39][41][42][43][44][47][48][49][50][51][52][53][54][55][56]…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The remainder reported using observational study designs (eg, pre-post studies, feasibility studies, pilot studies). Fifty-eight studies were conducted with primary care patients, [29][30][31][72][73][74]76,[78][79][80][81][82][83][84][85][86][87][88][89] 4 took place in a specialty clinics, 32,71,75,77 1 took place in urgent care, 27 and 3 took place across multiple settings (eg, primary, specialty, and urgent care). 26,28,90 Majority of studies reported including academic sites (n = 40), 29,[34][35][36][37][38][39][41][42][43][44][47][48][49][50][51][52][53][54][55][56]…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…28,[35][36][37][38]42,47,49,50,61,70,74,86,[88][89][90] Of note, 37 studies did not explicitly report how staff were trained to implement the program. 27,[32][33][34]40,41,43,45,[51][52][53][54][55][56]58,59,[62][63][64][65][66][67][68][69]71,73,[76][77][78][79][80][81][82][83][84][85]87…”
Section: Response Activitiesmentioning
confidence: 99%
“…Current literature describing efforts to screen and respond to social needs has focused on electronic health record (EHR) integration [27][28][29], provider perspectives [30][31][32][33], and patient acceptability, and has sometimes used implementation case studies [34][35][36]. This existing literature suggests that patients consider social needs S/ R an acceptable and important element of patientcentered care, but they recognize the limits of the health care sector's capacity to resolve unmet social needs.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly all prior studies have described implementation in clinics that engaged in a funded, researcher-driven implementation study 14 - 17 or were part of a larger healthcare system initiative. 18 Our study offers a window into the unfacilitated diffusion—or lack thereof—of new social-needs targeted tools and practices into small and mid-sized safety-net clinics, and contributes to the understanding of the adoption of referral platforms, which in comparison to social needs screening has received less attention.…”
Section: Discussionmentioning
confidence: 97%